Treatment with roscovitine and butyrolactone i prior to in vitro maturation alters blastocyst production - Maziero, Rosiara Rosária Dias [UNESP]; Guaitolini, Carlos Renato De Freitas [UNESP]; Paschoal, Daniela Martins [UNESP]; Crespilho, André MacIel; Monteiro, Bianca Andriolo [UNESP]; Lima, Jonathan Soares De; Sestari, Danielle Andressa Oliveira; Landim-Alvarenga, Fernanda Da Cruz [UNESP] (Cambridge University Press (CUP), 2019)
SummaryThis study evaluated the effects of oocyte meiosis inhibitors roscovitine (ROS) and butyrolactone I (BL-I) on in vitro production of bovine embryos. Bovine oocytes were maintained in pre in vitro maturation (pre-IVM) with 25 μM ROS or 100 μM BL-I for 24 h to delay meiosis and for 24 h in in vitro maturation (IVM). Following this treatment, the nuclear maturation index was evaluated. All embryos degenerated following this procedure. In the second set of experiments, oocytes were maintained for 6 or 12 h in pre-IVM with the following three treatments: ROS (25 μM or 12.5 μM), BL-I (100 μM or 50 μM) or a combination of both drugs (6.25 μM ROS and 12.5 μM BL-I). Oocytes were cultivated for 18 or 12 h in IVM. When a meiosis-inducing agent was used during pre-IVM for 24 h, more degenerated oocytes were observed at the end of the IVM period. This effect decreased when the meiotic blocking period was reduced to 6 or 12 h. No significant differences were observed in the blastocyst production rate of oocytes in pre-IVM for 6 h with ROS, BL-I, or ROS + BL-I compared with that of the control group (P > 0.05). However, inhibition of oocytes for 12 h resulted in decreased embryo production compared with that in the controls (P < 0.05). There was no difference in the post-vitrification embryo re-expansion rate between the study groups, showing that the meiotic inhibition for 6 or 12 h did not alter the embryo cryopreservation process.
Keywords: Bovine; Embryo production; Meiotic inhibitors; Nuclear maturation; Oocyte; Vitrification